Salt and Nitric Oxide Synthase Inhibition-Induced Hypertension: Kidney Dysfunction and Brain Anti-Oxidant Capacity - Oktar, Suleyman; Ilhan, Selcuk; Meydan, Sedat; Aydin, Mehmet; Yonden, Zafer; Gokce, Ahmet (Taylor & Francis Inc, 2010)
The specific aim of this study was to examine the effects of salt-loading on kidney function and brain antioxidant capacity. Wistar rats were divided into four groups: Control rats were given normal drinking water and no drug treatment for 2 weeks. LNNA group: rats were given normal drinking water and the nitric oxide (NO) inhibitor NG-nitro-L-arginine (L-NNA), 3 mg/kg/day. LNNA + Salt group: rats were given drinking water containing salt 2% and 3 mg/kg L-NNA. Salt group: rats were given drinking water containing salt 2% and no drug treatment. Basal blood pressure and the levels of serum BUN, creatinine, uric acid, cortisol, electrolyte, serum antioxidant capacity, and oxidative stress were measured. NO, superoxide dismutase (SOD), and catalase (CAT) levels were measured in the hypothalamus, brainstem, and cerebellum. Salt overload increased the blood pressure of the LNNA + Salt group. Salt-loading enhanced BUN, creatinine, sodium retention. High salt produced an increase in uric acid levels and a decrease in cortisol levels in serum. Additionally, the oxidative stress index in serum increased in the LNNA + Salt group. Salt-loading enhanced brain NO levels, but not SOD and CAT activity. L-NNA increased brain SOD activity, but not CAT and NO levels. In conclusion, salt-loading causes hypertension, kidney dysfunction, and enhances oxidative stress in salt-sensitive rats.
Keywords: kidney; hypertension; oxidative stress; superoxide dismutase; salt